Impacto del Covid-19 en el empleo formal en empresas con diez a más trabajadores en las regiones de selva baja periodo 2020-2021 - Rengifo Rengifo, Diana (2023)
The thesis impact of covid-19 on formal employment in companies with ten or more workers in the low jungle regions period 2020-2021, aims to analyze the impact of Covid - 19 on the behavior of the employment index in formal private companies ten or more workers in the regions of Loreto, San Martín and Ucayali in the period 2020 - 2021; The work is of an applied type, under the quantitative approach, at the descriptive level and of non-experimental design. The results indicate that Covid 19 had a negative impact on formal employment in companies with ten or more workers in the regions of Loreto San Martin and Ucayali; In the Loreto region, 44,372 formal jobs were lost; in 2021, 28,559 formal jobs were recovered compared to the base year 2019. In the San Martin region, in 2020, 25,426 formal jobs were lost and in the in 2021, formal jobs will be recovered and slightly exceed the jobs of 2019, reaching an increase of 4,666 formal jobs. In the Ucayali region in 2020, 29,222 formal jobs were lost and in 2021 what was lost is recovered and 752 new formal jobs are increased compared to 2019. The Loreto region was the one that had the greatest negative impact of the Covid - 19, is the only region of the lower jungle that as of December 2021 does not recover the number of workers formally employed in companies with ten or more workers than in 2019